Association between hand grip strength and exercise addiction: differences by sport category and sex among elite athletes - Karaoglu, B.; Ceviz, E.; Ünver, S.; Çiftçi, I.; Demir, G. T.; Güvendi, B.; Bulgay, C.; Alpay, M.; Ihasz, F.; Zoltan, A.; Kovacsik, R.; Somogyi, A.; et al. (Frontiers in Psychology, 2026)
Introduction: Handgrip strength (HGS) is a key indicator of upper-body strength and overall physical fitness. While its links to health and sports performance have been widely studied, its relationship with the risk of exercise addiction (REA) remains unclear. Thus, the present study examines the relationship between HGS and REA across various sports disciplines, sexes, and national contexts, aiming to deepen our understanding of their intricate interplay.